Faktor Pendorong dan Penarik Dalam Motivasi Kewirausahaan Perempuan di Kelurahan Tengah Kecamatan Kramat Jati Jakarta Timur - Alin Alianny; Febry Yeni Anwar; Nur Hamidah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Women play a pivotal role in strengthening entrepreneurship, particularly within household-based microenterprise sectors. However, women’s entrepreneurial motivation is not always directly driven by economic necessity or the attractiveness of available business opportunities. This study investigates the influence of push factors and pull factors on women’s entrepreneurial motivation in Tengah Subdistrict, Kramat Jati District, East Jakarta. Using a quantitative explanatory research design, data were collected from 30 women microentrepreneurs through five-point Likert-scale questionnaires administered via purposive sampling. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that push factors do not have a significant effect on women’s entrepreneurial motivation (β = −0.026; p = 0.953), leading to the rejection of the first hypothesis. Likewise, pull factors also show no significant influence (β = 0.562; p = 0.187), resulting in the rejection of the second hypothesis. These results indicate that women’s entrepreneurial motivation cannot be adequately explained solely through the push–pull framework and is likely shaped by broader psychological and social dimensions. Theoretically, this study underscores the limitations of the push–pull model in explaining women’s entrepreneurship within local community contexts. Practically, the findings suggest that empowerment programs should prioritize the development of internal motivational capacities. Future studies are encouraged to adopt more comprehensive models by incorporating psychological, social, and cultural variables.